The Relationship Between Referral of Touch and the Feeling of Ownership in the Rubber Hand Illusion - Reader, Arran T.; Trifonova, Victoria S.; Ehrsson, H. Henrik (Frontiers in Psychology, 2021)
The rubber hand illusion (RHI) is one of the most commonly used paradigms to examine the sense of body ownership. Touches are synchronously applied to the real hand, hidden from view, and a false hand in an anatomically congruent position. During the illusion one may perceive that the feeling of touch arises from the false hand (referral of touch), and that the false hand is one's own. The relationship between referral of touch and body ownership in the illusion is unclear, and some articles average responses to statements addressing these experiences, which may be inappropriate depending on the research question of interest. To address these concerns, we re-analyzed three freely available datasets to better understand the relationship between referral of touch and feeling of ownership in the RHI. We found that most participants who report a feeling of ownership also report referral of touch, and that referral of touch and ownership show a moderately strong positive relationship that was highly replicable. In addition, referral of touch tends to be reported more strongly and more frequently than the feeling of ownership over the hand. The former observations confirm that referral of touch and ownership are related experiences in the RHI. The latter, however, indicate that when pooling the statements one may obtain a higher number of illusion ‘responders’ compared to considering the ownership statements in isolation. These results have implications for the RHI as an experimental paradigm.